ORGANIZATIONAL JUSTICE AND AFFECTIVE COMMITMENT: THE MEDIATING ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT - Pooja Purang (Asian Academy of Management Journal, 2011)
Perception of fairness of employees is a guiding force of employee attitude and behaviours. However, the mechanism by which justice affects needs to be studied further. This study hypothesizes perceived organizational support mediates the relationship between organizational justice perceptions and affective commitment of employees. The study was conducted in a Multi-national organization operating in India in the service sector; the sample size is 71 employees. Baron and Kenny’s model of studying the mediating relationship was used. The findings showed that POS fully mediates the relationship between distributive justice and affective commitment and partially mediates the procedural justice and affective commitment relationship. This study highlights the importance of fairness and justice in organizations and identifies the mechanism by which employees’ perceptions of justice influence their loyalty and involvement.